LIPID LOWERING ACTIVITY OF FERONIA LIMONIA LEAF IN TRITON WR-1339 (TYLOXAPOL) INDUCED HYPERLIPIDEMIC RATS - Pandit, Kanika; Mishra, Ritu; S., Brijesh; Bhagwat, Ashok; Bhatt, Purvi (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objectives: The present study was undertaken to assess the lipid lowering activity of methanolic extract from Feronia limonia leaf in Triton WR-1339 induced hyperlipidemic rats. Methods: Hyperlipidemia was induced in rats by a single intraperitoneal (i.p) injection of Triton WR 1339 (300 mg/kg b.w.) and it showed sustained elevated levels of serum cholesterol and triglyceride levels. Methanolic extract of Feronia. limonia at dose of 125, 250 and 500 mg/kg b.w. was administered to triton induced hyperlipidemic rats. The serum was analysed for lipid profile and the result was compared to the triton control group. The results of the study were expressed as mean Â± S.D. and data was analysed by using one way analysis of variance (ANOVA) followed by Dunnett's multiple comparison tests. Values with P<0.05 were considered as significant. Results: Oral administration of methanolic extract of Feronia limonia to hyperlipidemic rats at a dose of 500 mg/kg b.w. exhibited significant reduction in serum lipid parameters like total cholesterol, triglycerides, low density lipoprotein, very low density lipoprotein. Significant elevation (p<0.001) in high density lipoprotein and fecal fat content was observed in treated group when compared to Triton WR-1339 control group. Conclusion: The present study demonstrates that methanolic extract of Feronia limonia has significant lipid lowering activity in Triton WR-1339 induced hyperlipidemia in rats.